Faktor yang Mempengaruhi Profitabilitas pada Perusahaan Industri Wadah dan Kemasan yang Terdaftar di Bursa Efek Indonesia - Sri Salvina Devi Maharani; Ferdawati Ferdawati; Josephine Sudiman (Akuntansi dan Manajemen, 2023)
Profitability is the potential of a business entity to generate income within a certain period of time. The management of a company must be able to consider the factors that affect the company's profitability because this profitability is a determinant of the company's success. This study aims to provide empirical evidence on the impact of cash conversion cycle, liquidity and company size on the profitability of companies in the container and packaging industry listed on the Indonesia Stock Exchange. The population of this study is companies in the packaging industry listed on the Indonesian Stock Exchange from 2018 to 2021, and the sampling was done by purposive sampling method, so 11 sample companies were selected. This data analysis method is a multiple regression analysis using the SPSS version 25 program, and the results of this study show that the cash conversion cycle has a negative impact on profitability, liquidity has a positive impact on profitability, firm size has been shown to have no effect in container and packaging industry companies listed on the Indonesia Stock Exchange.